Estimación de la población de Anadara tuberculosa (Bivalvia:Arcidae) en Sierpe-Térraba, Costa Rica. - Campos M, Jorge A (Universidad de Costa Rica, 1990)
A diagnosis of Anadara tuberculosa populations in the mangroves of the Forestry Reserve Sierpe-Térraba, was accomplished in June 1988. The bivalve is present in substrates with a salinity of. 16-29 0/00, and the chemical characteristics and organic malter content of the substrate do not determine the distribution of the species. Capture per tide was 200 - 300 individuals. Density was estimated in 1.1 A. tuberculosa! m2, for a total of 26 X 106 larger than 4.4 cm. Comparisons of the actual population structure in Sierpe-Térraba with a Pre-Columbian sample, and an Index of Resource Exploitation (IRE) based on modes of several samples from the Pacific coast of Costa Rica, indicate that Sierpe-Térraba holds the healthiest populations of this species.